DETERMINANTS OF CUSTOMER SATISFACTION IN INDOMARET PERMATA TANGERANG CONSUMERS - Narto, Eko; Tarto, Tarto; Rachma, Riqkha Adilla (Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study is to determine the Influence of Store Atmosphere and Service Quality on Customer Satisfaction at Indomaret Permata Tangerang. This study uses a quantitative approach. Sampling was 100 people. Data collection techniques and tools are as questionnaires or questionnaires. Descriptive data analysis techniques are used to find out the picture of respondents' response and data distribution, while inferential statistical analysis is for hypothesis testing. The data management is assisted by Microsoft Excel and SPSS software version 26. The results of the study showed that partially the Store Atmosphere had a positive and significant effect on Customer Satisfaction as shown by a count of 4,395> a table of 1,984 and a significance of 0.000. For the variable of Service Quality partially has a positive and significant effect on Customer Satisfaction, it is shown with a tcal value of 7,123> ttable 1,984. and a significance of 0.000. Simultaneously, the Store Atmosphere and Service Quality have a positive and significant effect on Customer Satisfaction, which is shown by the value of Fcal> Ftabel 145.951 > 3.09 and a significance of 0.000. The ability of the variables of Store Atmosphere and Service Quality in explaining Customer Satisfaction was 75.1% as shown by the magnitude of the R square of 0.195 while the remaining 24.9% was influenced by other factors that were not included in the research model.